Methods Of Planting High-Yielding Seed Varieties for Light Industrial Textile Equipment - J.N. Komilov (Genius Journals, 2022)
For light industry and textile equipment, it is necessary to determine the time and depth of sowing of fertile seed varieties depending on the soil conditions of each region and even each field. Cultivation between the rows at the right time is the most important event
Keywords: norm; term; soil; cultivator